P-4 ALBUMIN LEVELS HAVE STRONGASSOCIATION WITH MORTALITY IN COVID-19 INFECTED PATIENS - Martín Uriel Vázquez-Medina; Cesar Montejo-Velázquez; Cruz Vargas-De-León; Arcelia Carolina Barrón-Campos; José Antonio Almeyda-Farfán; Julián Gonzalo Gándara-Calderón; Claudia Pantaleón-Martínez; Nerina del Carmen Fernández-Martínez; Herrera-Maceda María del Rosario; Eira Cerda-Reyes (Annals of Hepatology, 2021)
Introduction: To optimize hospital management of COVID-19 patients it is important to have parameters that allow us to identify patient with an increased risk of death. Although hypoalbuminemia has been related with severity in COVID-19, there is no agreement of the albumin cutoff points with a potential clinical use. Additionally, a measure of strength of the association between albumin levels and mortality has not been reported.Therefore, the aim of this study is to evaluate if Child Pug albumin categories are associated with mortality and obtain the strength of the association. Methods: Patients admitted to hospitalization with a positive SARS CoV 2 PCR from 4 April to 24 June 2020 were analyzed. Three groups were formed based on Child-Pugh albumin categories. Death frequency were compared between groups and statistical significance of the difference were assessed using a Xi2 test, strength of association between albumin levels and death was evaluated with a Kendall´s Tau B test. Results: A total of 348 patients were studied, age was 54.4 ± 14.7 years, 250 (71.8%) were male and 182 patients died (52%). Association of Albumin level and Death is presented Table 1, Kendall Tau B shows that knowing albumin level improves in 32% the prediction of death and since it has a negative coefficient at a lower level of albumin, risk of death increase. Conclusions: Kendall´s Tau-B shows a strong association between Child-Pug albumin categories and death, so is possible it´s use in clinical decisions as a marker of severity.